Oversikt over store ekspedisjoner (Polarboken, 1954)
Keywords: Antarktis; ekspedisjoner

Finn- og blåhvalenes trekk i Antarktis = The movements of fin and blue whales in Antarctic waters - Brown, S G (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; hvaler; marin zoologi

Internasjonalt samarbeid i hvalmerking : "Enern"s tokt til Sydishavet i 1953 : the voyage of the "Enern" to the Antarctic 1953 = International co-operation in whale marking - Clarke, Robert; Ruud, Johan T (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Konsul Lars Christensen 70 år - Gunnestad, Alf (Polarboken, 1954)
Keywords: Antarktis; biografi

Et forsøk på måling av breforandring i Antarktis - Liestøl, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1954)
Publisher: Routledge
Keywords: Antarktis; glasiologi; isbreer; klimaendringer

Sledge dogs of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1954)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; sledehunder

Depth of polar ice caps. Dronning Maud Land, Antarctica - Robin, Gordon de Quetteville (The Geographical Journal, 1954)
Includes results of seismic soundings in Dronning Maud Land, Antarctica.
Keywords: Dronning Maud Land; glasiologi

Measurements of ice thickness in Dronning Maud Land - Robin, Gordon de Quetteville (Polar Record, 1954)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Internasjonalt samarbeid i hvalmerking : Annen del av "Enern"s tokt til Sydishavet 1953 og forsøk med hvalmerker utført på flytende kokerier sesongen 1954 : The second period of the voyage of the "Enern" to the Antarctic 1953 and trials with whale marks conducted on board floating factories in the season 1954 = International co-operation in whale marking - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Glaciology in Queen Maud Land: work of the Norwegian-British-Swedish Antarctix Expedition - Schytt, Valter (Geographical Review, 1954)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

Verdien av de meteorologiske observasjoner fra hvalkokeriene = The value of meteorological observations from whaling factory ships - Vowinckel, E (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; klima; meteorologi; observasjoner